Lifestyle Factors in Hypertension Drug Research: Systematic Analysis of Articles in a Leading Cochrane Report - Dan E. Wilson; Tashina Van Vlack; Brendin P. Schievink; Eric B. Doak; Jason S. Shane; Elizabeth Dean (International Journal of Hypertension)
Established standards for first-line hypertension management include lifestyle modification and behavior change. The degree to which and how lifestyle modification is systematically integrated into studies of first-line drug management for hypertension is of methodological and clinical relevance. This study systematically reviewed the methodology of articles from a recent Cochrane review that had been designed to inform first-line medical treatment of hypertension and was representative of high quality established clinical trials in the field. Source articles (n=34) were systematically reviewed for lifestyle interventions including smoking cessation, diet, weight loss, physical activity and exercise, stress reduction, and moderate alcohol consumption. 54% of articles did not mention lifestyle modification; 46% contained nonspecific descriptions of interventions. We contend that hypertension management research trials (including drug studies) need to elucidate the benefits and risks of drug-lifestyle interaction, to support the priority of lifestyle modification, and that lifestyle modification, rather than drugs, is seen by patients and the public as a priority for health professionals. The inclusion of lifestyle modification strategies in research designs for hypertension drug trials could enhance current research, from trial efficacy to clinical outcome effectiveness, and align hypertension best practices of a range of health professionals with evidence-based knowledge translation.